Implementasi Harmonisasi Ilmu Sains dan Agama di Kelas 8 Pondok Pesantren Nurul Huda Banat Pekalongan - Zahwa, Syafira; Salsabila, Nilna; Ramadhani, Mutiara Sofia; Ariza, Said Fachri (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
This community service activity was conducted at Pondok Pesantren Nurul Huda Banat in Pekalongan, aiming to enhance the understanding of 8th-grade MTs students regarding the harmonization between science and religion. The main issue addressed was the students’ limited comprehension of the interrelation between these two fields. Through face-to-face socialization and interactive discussions, the program presented material covering the concept, objectives, implementation, and challenges of science-religion harmonization in the context of pesantren education. Evaluation results indicated a significant improvement in participants' understanding, increasing from 0% to 100% after the activity. This initiative demonstrates that a contextual approach can effectively foster integrative and critical thinking among students and encourage the development of a pesantren generation that balances intellectual and spiritual growth.